Hubungan Pengalaman Kerja terhadap Profesionalitas Guru di Sekolah Dasar Negeri Kota Palangka Raya - Syariah (Universitas Insan Budi Utomo, 2024)
This study aims to investigate the relationship between teachers' work experience and work motivation towards the professionalism of teachers in State Elementary Schools (SDN) in Cluster XVI, Bukit Batu Subdistrict, Palangka Raya City. The research employs a quantitative approach with a correlational ex-post facto design. The study's respondents involve 45 teachers comprising civil servants (PNS), contractual teachers (PPPK), and honorary teachers across seven SDNs, namely SDN 1 Tangkiling, SDN 2 Tangkiling, SDN 3 Tangkiling, SDN 4 Tangkiling, SDN 1 Sei Gohong, SDN 2 Sei Gohong, and SDN Kanarakan. The findings reveal a positive relationship between teachers' work experience and teacher professionalism in SDNs in Cluster XVI, Bukit Batu Subdistrict, Palangka Raya City, with work experience influencing teacher professionalism by 34.5%. The study also identifies a positive relationship between teacher motivation and teacher professionalism in SDNs in Cluster XVI, Bukit Batu Subdistrict, Palangka Raya City, with motivation's impact on teacher professionalism reaching 37.5%. Furthermore, the research uncovers a positive relationship between work experience and teacher motivation towards teacher professionalism in SDNs in Cluster XVI, Bukit Batu Subdistrict, Palangka Raya City. The analysis indicates that between teachers' work experience and teacher motivation has a significant influence of 49.8% on teacher professionalism. These research findings provide crucial insights for educational administrators and policymakers to enhance teacher professionalism by considering the aspects of work experience and teacher motivation in the environment of SDNs in Cluster XVI, Bukit Batu Subdistrict, Palangka Raya City.